Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jmri.28492
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of MRI‐Invisible Early‐Stage Endometrial Cancer With MRI‐Based Radiomics Analysis

Abstract: BackgroundRadiomics‐based analyses have demonstrated impact on studies of endometrial cancer (EC). However, there have been no radiomics studies investigating preoperative assessment of MRI‐invisible EC to date.PurposeTo develop and validate radiomics models based on sagittal T2‐weighted images (T2WI) and T1‐weighted contrast‐enhanced images (T1CE) for the preoperative assessment of MRI‐invisible early‐stage EC and myometrial invasion (MI).Study TypeRetrospective.PopulationOne hundred fifty‐eight consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(103 reference statements)
1
1
0
Order By: Relevance
“…In the present study, the combination of T2WI and T1CE sequences showed the highest prediction performance among all combinations of sequences. This was consistent with the results reported by Jiang et al [23] , who found that a radiomics model using T2WI and T1CE sequences provided good performance for detecting MRI-invisible early-stage endometrial cancer and myometrial invasions. Hu et al [24] combined T1CE and T2WI radiomics analysis of cervical mucosa to predict early cervical cancer not visible by MRI.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the combination of T2WI and T1CE sequences showed the highest prediction performance among all combinations of sequences. This was consistent with the results reported by Jiang et al [23] , who found that a radiomics model using T2WI and T1CE sequences provided good performance for detecting MRI-invisible early-stage endometrial cancer and myometrial invasions. Hu et al [24] combined T1CE and T2WI radiomics analysis of cervical mucosa to predict early cervical cancer not visible by MRI.…”
Section: Discussionsupporting
confidence: 92%
“…In a parallel development, Yan, Ma et al [20] developed a nomogram for predicting ovarian preservation in early-stage EC, achieving an AUROC of 0.96, thereby surpassing the performance of radiologists (0.80 and 0.86). To address the challenge of detecting non-visible EC in MRI, Jiang's team [21] developed two radiomics models for distinguishing non-visible EC and MI, both demonstrating excellent performance with average AUROCs of 0.896 and 0.844, respectively. The current body of research indicates that classifiers based on radiomics features, either standalone or in conjunction with selected clinical and traditional imaging features, hold high diagnostic efficacy, potentially matching or exceeding the capabilities of seasoned radiologists, thereby enhancing diagnostic precision.…”
Section: Evaluation Of Myometrial Invasion Depth In Initial Stages Of...mentioning
confidence: 99%
“…4 In this issue of the Journal of Magnetic Resonance Imaging, Chen et al apply radiomic analysis to patients suspected of having endometrial cancer without visible lesions at MR imaging. 5 They examined a total of 2074 imaging features in 130 patients with MRI-invisible suspected endometrial pathology. Threedimensional regions of interest were placed on T2-weighted images and T1-weighted images obtained after gadolinium contrast.…”
mentioning
confidence: 99%